EFFEKTIVITAS PEMANFAATAN MEDIA BLOG MENINGKATKAN KEMAMPUAN SISWA DALAM PEMBELAJARAN MENULIS CERPEN DI KELAS XI SMA NEGERI 2 LAWE BULAN - Dwi Azura; James Marudut; Rekaza Akbar (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This study aims to determine the improvement of short story writing skills through the use of blog media in class XI students of SMA Negeri 2 Lawe Bulan in the 2021/2022 academic year. The population in this study were all students of class XI and a sample of 36 people. The method used in this study is an experimental method with a one group pretest and posttest design with data analysis using the "t" test. From data processing, it was found that the average value of the initial test of short story writing skills by students was 52.10 and was included in the poor category, with a standard deviation of 6.09 and an increase in the final test score with an average value of 87.36 and included in the good category, with a standard deviation of 7.33. Based on the results of the students' initial and final test scores and if it is associated with the KKM value of Indonesian language subjects for high school, it is 70, the students' short story writing ability is included in the good category. From hypothesis testing, it is obtained that the value of t count = 24.19 and in consultation with the value of t_table at a significant level of 5% = 2,030, thus t_count > t_table or 24.19 > 2,030 then the hypothesis is accepted. So it can be concluded that there is an increase in the ability to write short stories through the use of blog media in class XI students of SMA Negeri 2 Lawe Month in the 2021/2022 Academic Year.